Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen Pada PT. Tri Sakti Purwoasri Makmur Indonesia Propinsi Lampung - Yateno; Durotun Nasikah; Nanang Wahyudin (Jurnal Manajemen DIVERSIFIKASI, 2024)
Consumer satisfaction is a scourge of success in a company in maintaining its products andpersuading consumers to make purchases, so this research aims to examine both partiallyand simultaneously the effect of product quality and price on customer satisfaction at PT. TriSakti Lampung Group. The research design uses a quantitative approach with a total sampleof 52 consumers. The sampling technique is Purposive Sampling. While the data analysistechnique used is a questionnaire and tests the questionnaire by testing validity, reliability,and prerequisite analysis tests, namely normality, homogeneity, linearity and multipleregression through partial t tests and simultaneous tests. The results of the analysis provethat partially product quality and price have an influence on consumer satisfaction in makingtransactions to buy products sold at PT. Group Magic Tricks